Correlation between the radiological observation of isolated tertiary waves on an esophagram and findings on high-resolution esophageal manometry. Issue 1 (1st January 2016) - Halland, M.; Ravi, K.; Barlow, J.; Arora, A.
Summary: Barium esophagrams are a frequently performed test, and radiological observations about potential abnormal esophageal motility, such as tertiary contractions, are commonly reported. We sought to assess the correlation between tertiary waves, and in particular isolated tertiary waves, on esophagrams and findings on non-synchronous high-resolution esophageal manometry. We retrospectively reviewed reports of esophagrams performed at a tertiary referral center and identified patients in whom tertiary waves were observed and a high-resolution esophageal manometry had been performed. We defined two groups; group 1 was defined as patients with isolated tertiary waves, whereas group 2 had tertiary waves and evidence of achalasia or an obstructing structural abnormality on the esophagram. We collected data on demographics, dysphagia score, associated findings on esophagram, and need for intervention. We reviewed the reports of 2100 esophagrams of which tertiary waves were noted as an isolated abnormality in 92, and in association with achalasia or a structural obstruction in 61. High-resolution manometry was performed in 17 patients in group 1, and five had evidence of a significant esophageal motility disorder and 4 required any intervention. Twenty-one patients in group 2 underwent manometry, and 18 had a significant esophageal motility disorder. An isolated finding of tertiary waves on an esophagram is rarely associated with a significant esophageal motility disorder that requires intervention. All patients with isolated tertiary waves who required intervention had a dysphagia to liquids. Tertiary contractions, in the absence of dysphagia to liquids, indicate no significant esophageal motility disorder.